2017
DOI: 10.1186/s13045-017-0433-z
|View full text |Cite
|
Sign up to set email alerts
|

Severe nivolumab-induced pneumonitis preceding durable clinical remission in a patient with refractory, metastatic lung squamous cell cancer: a case report

Abstract: BackgroundProgrammed cell death 1 (PD-1) and its ligand 1 (PD-L1) inhibitors have quickly become standard of care for patients with advanced non-small cell lung cancer and increasing numbers of other cancer types. In this report, we discuss the clinical history, pathological evaluation, and genomic findings in a patient with metastatic lung squamous cell cancer (SCC) who developed severe nivolumab-induced pneumonitis preceding durable clinical remission after three doses of nivolumab.Case presentationA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
(36 reference statements)
0
28
0
2
Order By: Relevance
“…25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival. Case reports have suggested an increased risk of pneumonitis in patients who had previously received TRT 26,27 ; however, the recent PACIFIC trial (a global study to assess the effects of MEDI4736 following concurrent chemoradiation in patients with stage III unresectable non-small cell lung cancer) did not show a…”
Section: Discussionmentioning
confidence: 97%
“…25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival. Case reports have suggested an increased risk of pneumonitis in patients who had previously received TRT 26,27 ; however, the recent PACIFIC trial (a global study to assess the effects of MEDI4736 following concurrent chemoradiation in patients with stage III unresectable non-small cell lung cancer) did not show a…”
Section: Discussionmentioning
confidence: 97%
“…Clinical evidence has suggested that patients can experience long-term PFS if the immune checkpoint inhibitor is discontinued due to side effects in response [1,[11][12][13]. Interestingly, a recent neoadjuvant study in the field of NSCLC has shown that 45% of patients show major tumor responses even after a short (4 weeks) PD-1 therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports, patient series, and DOI: 10.1159/000493193 clinical trials have shown that patients whose immune checkpoint inhibitor therapy has been discontinued due to severe side effects can experience prolonged responses without need for further treatment [1,[11][12][13]. A single prospective study has addressed the treatment length of PD-1 agents in non-small-cell lung cancer (NSCLC), randomizing responding patients to either discontinue the PD-1 agent at 1 year or continuing therapy until progression.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in up to 4% of all-grade irAEs and 1.5% of high-grade irAEs in clinical trials [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Pneumonitis tended to occur early, at a median time of 4.5 weeks (IQR, 2.75-6.25) in four patients described in three case reports, all of whom were treated with nivolumab (Additional file 4: Table S3) [37,40,42]. The median duration of immune treatment was 4.5 (IQR, 2.75-6.25) cycles, implying that immunotherapy did not stop immediately when pneumonitis occurred.…”
Section: Nature Of Iraesmentioning
confidence: 99%